Effect of climate warming on the annual terrestrial net ecosystem CO2 exchange globally in the boreal and temperate regions - Zhiyuan Zhang; Renduo Zhang; Cescatti, A.; Wohlfahrt, G.; Buchmann, Nina; Juan Zhu; Guanhong Chen; Moyano, F.; Pumpanen, J.; Takashi Hirano; Kentaro Takagi; Merbold, Lutz (Springer, 2017)
The net ecosystem CO2 exchange is the result of the imbalance between the assimilation process (gross primary production, GPP) and ecosystem respiration (RE). The aim of this study was to investigate temperature sensitivities of these processes and the effect of climate warming on the annual terrestrial net ecosystem CO2 exchange globally in the boreal and temperate regions. A database of 403 site-years of ecosystem flux data at 101 sites in the world was collected and analyzed. Temperature sensitivities of rates of RE and GPP were quantified with Q10, defined as the increase of RE (or GPP) rates with a temperature rise of 10 °C. Results showed that on the annual time scale, the intrinsic temperature sensitivity of GPP (Q10sG ) was higher than or equivalent to the intrinsic temperature sensitivity of RE (Q10sR ). Q10sG was negatively correlated to the mean annual temperature (MAT), whereas Q10sR was independent of MAT. The analysis of the current temperature sensitivities and net ecosystem production suggested that temperature rise might enhance the CO2 sink of terrestrial ecosystems both in the boreal and temperate regions. In addition, ecosystems in these regions with different plant functional types should sequester more CO2 with climate warming.